Monitoreo de incendios forestales con drones en la Reserva de Usos Múltiples Guaraní = Monitoring of forest fires with drones in the Reserva de Usos Múltiples Guaraní - Hildt, Eduardo; Orona, Martín (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2024)
This article analyzes a wildfire monitoring experience using drones in the Reserva de Usos Múltiples Guaraní. Three different drones were employed. The DJI Phantom 3 Pro, a large drone, effectively operated from an open area, while the smaller DJI Air 2S and DJI Mavic Mini were used in various locations. The DJI Air 2S offered digital zoom capabilities for enhanced fire observation, whereas the DJI Mavic Mini faced radio link challenges due to dense vegetation. The drones provided valuable information for coordinating firefighting efforts, primarily the location of the fire sources and the extension and direction of the fire fronts.